Journal of Applied Animal Nutrition (Cambridge)
Journal of Applied Animal Nutrition publishes leading research in all aspects of animal feed science and nutrition in agricultural species, companion species and exotic species. Research areas covered include commercially funded research such as new product development as well as academic research. The breadth and quality of original research articles, review articles and pilot studies describing large-scale trials make the journal invaluable to practitioners, consultants and veterinarians as well as researchers in the public and private sectors.
Keywords: Nutrition